Is the High Frequency of Machado-Joseph Disease in China Due to New Mutational Origins? - Li, Tianjiao; Martins, Sandra; Peng, Yun; Wang, Puzhi; Hou, Xiaocan; Chen, Zhao; Wang, Chunrong; Tang, Zhaoli; Qiu, Rong; Chen, Chao; Hu, Zhengmao; Xia, Kun; et al. (Frontiers in Genetics, 2019)
Machado-Joseph disease (MJD, also known as spinocerebellar ataxia 3 or SCA3) is the most common dominant ataxia worldwide, with an overall average prevalence of 1-5/100,000. To this date, two major ancestral lineages have been found throughout the world. In China, the relative frequency of MJD among the SCAs reaches as high as 63%; however, little is known about the mutational origin of MJD/ SCA3 in this country. We analysed 50 families with MJD patients in two or more generations to study the hypothesis that new mutational events have occurred in this population. Haplotypes based on 20 SNPs have shown new genetic backgrounds segregating with MJD mutations in our cohort from China. We found the “Joseph-derived” lineage (Joseph lineage with a G variant in rs56268847) to be very common among Chinese MJD patients. Moreover, we estimated the time since the origin of this MJD SNP background based on STR diversity flanking the (CAG)n of ATXN3. It is surprising to find that the Chinese MJD population originated from 8600 to 15,000 years ago, far earlier than the previous literature reports, which will be an important evidence to explain the origin, spread and founder effect of MJD.